An essential role of the basal body protein SAS‐6 in Plasmodium male gamete development and malaria transmission. (24th September 2014) - Marques, Sara R.; Ramakrishnan, Chandra; Carzaniga, Raffaella; Blagborough, Andrew M.; Delves, Michael J.; Talman, Arthur M.; Sinden, Robert E.
Summary Gametocytes are the sole Plasmodium parasite stages that infect mosquitoes; therefore development of functional gametes is required for malaria transmission. Flagellum assembly of the Plasmodium male gamete differs from that of most other eukaryotes in that it is intracytoplasmic but retains a key conserved feature: axonemes assemble from basal bodies. The centriole/basal body protein SAS‐6 normally regulates assembly and duplication of these organelles and its depletion causes severe flagellar/ciliary abnormalities in a diverse array of eukaryotes. Since basal body and flagellum assembly are intimately coupled to male gamete development in Plasmodium, we hypothesized that SAS‐6 disruption may cause gametogenesis defects and perturb transmission. We show that Plasmodium berghei sas6 knockouts display severely abnormal male gametogenesis presenting reduced basal body numbers, axonemal assembly defects and abnormal nuclear allocation. The defects in gametogenesis reduce fertilization and render Pbsas6 knockouts less infectious to mosquitoes. Additionally, we show that lack of Pbsas6 blocks transmission from mosquito to vertebrate host, revealing an additional yet undefined role in ookinete to sporulating oocysts transition. These findings underscore the vulnerability of the basal body/SAS‐6 to malaria transmission blocking interventions.